A new improved strategy for the selection of cold-adapted antagonist yeasts to control postharvest pear diseases - Lutz, María Cecilia (2012)
Postharvest diseases cause considerable losses of harvested fruits during transportationand storage. Many yeast species have been reported as good antagonistsagainst postharvest pear pathogens. In this work, we used a novel selection strategythat involves the isolation of yeasts from washing fluids, showing biocontrolactivity against a regional Penicillium expansum strain (primary screening),originally obtained from fruit wounds after long time storage at 1/08C. About26 isolates representative of the 11 yeast species identified in the 27 selectedwashing waters were chosen to be evaluated in a secondary screening against aregional Botrytis cinerea strain on pear wounds. Among yeasts tested, 38% showedcomplete control of P. expansum, but only 15% reduced the decay incidence ofB. cinerea to 6080% at 1/08C. These results reveal that some of the yeasts foundcan be biological alternatives to fungicides in the control of P. expansum andB. cinerea infections. Based on the data obtained, our strategy seems to be muchmore effective than the previously reported methods in obtaining successfulbiocontrol agents.